2008
DOI: 10.1007/s11010-008-9743-3
|View full text |Cite
|
Sign up to set email alerts
|

Simulated microgravity activates apoptosis and NF-κB in mice testis

Abstract: Microgravity is known to have significant effect on all aspects of reproductive function in animal models. Recent studies have also shown that microgravity induces changes at the cellular level, including apoptosis. Our effort here was to study the effect of simulated microgravity on caspase-8 and the caspase-3 activities, the effectors of the apoptotic pathway and on the transcription factor NF-kappaB a signaling molecule in mouse testis. Morey-Holton hind limb suspension model was used to simulate microgravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 44 publications
1
16
1
Order By: Relevance
“…Stress lead to multiple signals with varied responses in different organs and subjects (Stein 2002). Mice subjected to HLS, induce oxidative stress, lipid peroxidation, activate NFκB damaging many regions of brain (Wise et al 2005), and also induce apoptosis in testis (Sharma et al 2008). In the present study the liver weight of HLS mice significantly decreased compared to control.…”
Section: Discussionsupporting
confidence: 42%
“…Stress lead to multiple signals with varied responses in different organs and subjects (Stein 2002). Mice subjected to HLS, induce oxidative stress, lipid peroxidation, activate NFκB damaging many regions of brain (Wise et al 2005), and also induce apoptosis in testis (Sharma et al 2008). In the present study the liver weight of HLS mice significantly decreased compared to control.…”
Section: Discussionsupporting
confidence: 42%
“…There was a significant increase in the number of cells within the superficial epithelium that exhibited signs of apoptosis in simulated microgravity treatments compared to gravity controls. Previous studies have shown that simulated microgravity can cause an increase in cellular apoptosis in a wide range of cell types, including osteoblasts, reproductive, and endothelial cells4849. A common mechanism associated with the increase in simulated microgravity-induced apoptosis in these cell types was the activation and upregulation of the NF-κB pathway4849.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiment, we cannot rule out the possibility of participation of other UBQTN family members in the degradation of IB and activation c-REL/NF-B in rotated cells. Sharma et al (43) showed that exposure of mice to simulated microgravity using hind limb suspension resulted in increased activation of NF-B in testis.…”
Section: Genesmentioning
confidence: 99%